Ilustracja słów Pisma Świętego jako element polemiki międzywyznaniowej w dobie kontrreformacji na przykładzie obrazu Trójca Święta w kościele pojezuickim w Twardocicach. - Kłoda, Emilia (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
At the beginning of the 18th century, Jesuits came to Twardocice in order to stop the local movement of Schwenkfelders – the supporters of the Silesian radical mystical reformer Kaspar von Schwenkfeld. In consequence, the aggressive Jesuit action led to the elimination of the religious group in the region. A chapel devoted to Holy Trinity was built in Twardocice as a symbol of the Catholic Church’s triumph. The iconographic program of a painting in the main altar could be interpreted as a reflection of the ongoing interconfessional polemic. The painting with a carefully selected Bible quotation became a theological treatise designed to proclaim the only possible way to God and to legitimize the Jesuit intervention.